Alteration of Fermentative Metabolism Enhances Mucor circinelloides Virulence - Díaz-Pérez, Sharel P.; Patiño-Medina, J. Alberto; Valle-Maldonado, Marco I.; López Torres, Adolfo; Jácome-Galarza, Irvin E.; Anaya-Martínez, Verónica; Gómez-Ruiz, Verónica; Campos-García, Jesús; Nuñez-Anita, Rosa E.; Ortiz-Alvarado, Rafael; Ramírez-Díaz, Martha I.; Gutiérrez-Corona, J. Felix; et al. (Infection and Immunity, 2020)
The fungus Mucor circinelloides undergoes yeast-mold dimorphism, a developmental process associated with its capability as a human opportunistic pathogen. Dimorphism is strongly influenced by carbon metabolism, and hence the type of metabolism likely affects fungal virulence. We investigated the role of ethanol metabolism in M. circinelloides virulence. A mutant in the adh1 gene (M5 strain) exhibited higher virulence than the wild-type (R7B) and the complemented (M5/pEUKA-adh1⁺) strains, which were nonvirulent when tested in a mouse infection model. Cell-free culture supernatant (SS) from the M5 mutant showed increased toxic effect on nematodes compared to that from R7B and M5/pEUKA-adh1⁺ strains. The concentration of acetaldehyde excreted by strain M5 in the SS was higher than that from R7B, which correlated with the acute toxic effect on nematodes. Remarkably, strain M5 showed higher resistance to H₂O₂, resistance to phagocytosis, and invasiveness in mouse tissues, and induced an enhanced systemic inflammatory response compared with R7B. Mice infected with strain M5 under disulfiram treatment exhibited only half the life expectancy of those infected with M5 alone, suggesting that acetaldehyde produced by M. circinelloides contributes to the toxic effect in mice. These results demonstrate that failure in fermentative metabolism, specifically in the ethanol production step in M. circinelloides, contributes to its virulence, inducing a more severe tissue burden and inflammatory response in mice as a consequence of acetaldehyde overproduction.
Keywords: Mucor circinelloides; Metabolismo fermentativo; Alcohol deshidrogenasa; Virulencia